2013
DOI: 10.1039/c2sc21516k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-assisted linker exchange (SALE) and post-assembly metallation in porphyrinic metal–organic framework materials

Abstract: Using recently reported robust porphyrinic metal-organic framework (RPM) materials, we have examined the systematic exchange of pillaring linkers/struts as a means of accessing new versions of these materials.Dipyridyl-porphyrin Zn(II) (Zn-dipy) struts were successfully replaced by M 2 -dipy (M 2 ¼ 2H(+), Al(III), Sn(IV)), forming crystalline solid solutions of Zn(Zn 1Àx M x )-RPM in variable ratios. In addition, post-synthetic metallation was demonstrated using Zn2H-RPM, again with retention of crystallinity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 33 publications
1
101
0
Order By: Relevance
“… ii) The size of the MOF crystals . Smaller crystal sizes enable a faster rate of ligand exchange compared to larger crystals due to the faster diffusion rate iii) The choice of solvent .…”
Section: Strategies For Improving the Functionality Of Zifsmentioning
confidence: 99%
“… ii) The size of the MOF crystals . Smaller crystal sizes enable a faster rate of ligand exchange compared to larger crystals due to the faster diffusion rate iii) The choice of solvent .…”
Section: Strategies For Improving the Functionality Of Zifsmentioning
confidence: 99%
“…10b,13 Recently, the replacement of the structure-building organic linkers has been utilized in the synthesis or functionalization of MOFs, including ZIFs, UiO and bio-MOFs. 10b, [12][13][14] Here, we report the use of ZIF-7 as the template to synthesize benzotriazole-containing ZIF (ZIF-7-M) without changing the framework via a PSE approach (Scheme 1). However, introducing new ligands with more coordinative atoms is challenging.…”
mentioning
confidence: 99%
“…Li et al [43], reported the synthesis of new metal organic polyhedral (MOPs) from the replacement of organic linkers in three different Cu based MOPs thus allowing the as synthesized structure to take on new pore sizes/shapes and functionalities. Burnett et al [22], also reported linker exchange reactions in multidimensional materials, 2-D and 3-D MOFs, while Takaishu et al [44], reported new porphyrininic MOFs by exchanging the pillaring linkers. Mesoporous MOFs were also investigated for linker exchange; Li et al [45] demonstrated the exchange of dicarboxylate linkers from mesoporous bio-MOF-100, generating isoreticular bio-MOF analogs 101-103.…”
Section: Linker Exchangementioning
confidence: 95%